STATINS IN CHRONIC KIDNEY DISEASE. IS THERE A DRUG OF CHOICE? - O. M. Drapkina; O. N. Korneeva (Кардиоваскулярная терапия и профилактика, 2015)
Chronic kidney disease (CKD) is related to increased cardiovascular risk, and requires thorough dyslipidemia control. Statin therapy is expedient for prevention and treatment of cardiovascular disorders in CKD patients. The opportunities are reviewed for the use of statins in these patients, efficacy and safety at different stages of CKD, the need for dosage correction and choice of the exact drug. The comparison performed, benefits and misconveniences discussed of rosuvastatin and atorvastatin in CKD.